Peningkatan Respon Imun Non-Spesifik Benih Kerapu Bebek, Cromileptes altivelis dengan Imunostimulan dan Bakterin terhadap Infeksi Viral Nervous Necrosis (VNN) - Des Roza; Fris Johnny; Tridjoko Tridjoko (Universitas Gadjah Mada, 2006)
An experiment to evaluate the effectiveness immunostimulant and bacterin on humpback grouper have been conducted at the Disease Laboratory of Research Institute for Mariculture, Gondol, Bali. The experiment was designed in completely randomized design with four treatments in duplicates. Two hundred of humpback grouper juveniles (15-18 cm of total length, 55-65 g of body weight) were injected intraperitoneally with (A) bacterine at 107 cfu/kg body weight (BW), (B) peptidoglycan at 100 mg/kg BW, and (C) immuno star at 100 ml/kg BW, (D) control. The fish were then challenged with VNN by intramuscular injection at 10 days post treatment. Results showed that survival rates of juvenile after challenged with VNN were 60.00% (B & C), 53.34% (A), and 1.67% (control). Parameters of non-spesific immune respons showed that phagocytic activities were 17.56% (B), 17.55% (C), 13.11% (A), and 9.33% (control). In addition, lisozyme activities were 1.64 cm (B), 1.58 cm (C), 1.55 cm (A), and 1.46 cm (control). Immunostimulant and bacterin stimulated non-specific immune response, and increased survival rate of humpback grouper juvenile.